Determinant on The Structural Performance of Krisnadwipayana University - Lina Tio; Dorris Yadewani; Ali Ameen; Ibrahin Alrajawy (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The rise of knowledge-based technopreneurship has led to significant changes in work and the demands placed on organizations. Organizations are required to become a repository of innovation and nurture and retain talent resources. The primary purpose of this study is to investigate the impact that technological entrepreneurship, process innovation, and administrative innovation have had on the structural performance of Krisnadwipayana University. Students who made use of various smart government services were selected through a process known as random sampling. A total of 700 respondents were asked to participate in the survey, but only 403 did so, yielding a response rate of 57.57%. After removing missing data, outliers, and questionable replies, 372 respondents were evaluated. SmartPLS 3.0 was used to analyze research models using PLS and SEM-VB. The findings of this study add to what is known about technopreneurship in the academic and public sectors. They look at how innovations in technology, processes, and management affect the academic and administrative success of Krisnadwipayana University students.